Improvement of Bananas through Gamma Ray Irradiation (2013)
Banana is the second most widely-grown fruit crop in the Philippines and considered as the number one dollar earner and export winner. Out of the diverse types and kinds of banana, cultivar ‘Lakatan’ is the most popular in the domestic and to some extent in the export market. However, no improvement and breeding activities for this crop in the Philippines has been done due to its long life cycle and sterility trait. In order to address this, mutation breeding through gamma irradiation can be an alternative solution. This research was conducted to determine the LD50 for ‘Lakatan’ (shoot tips) and two variants (embryo and cell suspension), and to develop a ‘Lakatan’ cultivar with improved postharvest trait. Radio sensitivity test on shoot tip cultures established that the LD50 is the 50Gy gamma ray. Mutation introduction was carried out for 500 shoot tips using 50Gy gamma ray treatment. Gamma irradiated plants were evaluated for four generations. Mutation were observed in the bunch weight, number of hands per bunch, number of fingers per hand, and shelf life. Hence, the preliminary findings suggest the potential of induced mutation through gamma ray irradiation as an alternative technique in developing/generating bananas with specific traits of interest.